The Parāvidyā–Aparāvidyā paradigm in Hindu epistemology as a foundational framework for Hindu higher education in Indonesia - Donder, I Ketut; Behura, Ajit Kumar; Maheswari, Prasanthy Devi (Dharmakirti : International Journal of Religion, Mind and Science, 2025)
Background: The Parāvidyā–Aparāvidyā paradigm serves as a foundational epistemological framework within the Hindu knowledge system, emphasizing the integration of material (aparā) and spiritual-transcendental (parā) dimensions. This article critically examines the relevance and urgency of this paradigm as a basis for constructing a distinct Hindu epistemology, particularly in the context of developing curricula and the educational vision of Hindu Higher Education in Indonesia. Through a philosophical analysis of primary sources such as the Muṇḍaka Upaniṣad, Chāndogya Upaniṣad, and Vedānta Sūtra, this study argues that the Parāvidyā Aparāvidyā framework not only bridges empirical and spiritual knowledge, but also offers a viable alternative to the hegemony of the Western positivist paradigm that has long dominated educational systems.  Methods: Employing a qualitative-hermeneutic and conceptual approach, this paper demonstrates that the application of this paradigm can foster a holistic educational model grounded in values of civility, spirituality, and self-awareness. Finding: The findings indicate that while awareness of the duality between spiritual and worldly knowledge is growing within Hindu Religious Higher Education Institutions/Perguruan Tinggi Keagamaan Hindu (PTKH), its implementation remains limited and has not yet been systematically integrated into curricula, pedagogy, or assessment practices. The findings recommend a reformulation of the epistemological orientation of Hindu Higher Education toward a learning system that balances sakala and niskala aspects, thus better equipping it to address contemporary civilizational challenges in a sustainable and Dharma-based manner. Conclusion: Through a hermeneutic and transdisciplinary approach, this research has constructed an alternative epistemic model DIKWP (Data–Information–Knowledge–Wisdom–Peace), which not only expands the conventional DIKW framework but also enriches the spiritual dimension of intellectual formation. True knowledge, from a Hindu perspective, does not culminate in wisdom alone but must result in inner transformation, manifesting as peace (śānti) and spiritual liberation (mokṣa). Novelty/Originality of this article: The novelty of this study lies in its philosophical reconstruction of the Parāvidyā–Aparāvidyā paradigm as a comprehensive epistemological framework for Hindu Higher Education in Indonesia.